Swiss S1 guideline for the treatment of rosacea. (21st August 2017) - Anzengruber, F.; Czernielewski, J.; Conrad, C.; Feldmeyer, L.; Yawalkar, N.; Häusermann, P.; Cozzio, A.; Mainetti, C.; Goldblum, D.; Läuchli, S.; Imhof, L.; Brand, C.; et al.
Abstract: Rosacea (in German sometimes called 'Kupferfinne', in French 'Couperose' and in Italian 'Copparosa') is a chronic and frequently relapsing inflammatory skin disease primarily affecting the central areas of the face. Its geographic prevalence varies from 1% to 22%. The differential diagnosis is wide, and the treatment is sometimes difficult and varies by stage of rosacea. For erythematous lesions and telangiectasia, intense pulsed light (IPL) therapy and lasers are popular treatment option. In addition, a vasoconstrictor agent, brimonidine, has recently been developed. For papulopustular rosacea, topical antibiotics, topical and systemic retinoids, as well as systemic antibiotics are used. A topical acaricidal agent, ivermectin, has undergone clinical development and is now on the market. In the later stages, hyperplasia of the sebaceous glands develops, resulting in phymatous growths such as the frequently observed bulbous nose or rhinophyma. Ablative laser treatments have largely replaced classical abrasive tools. Here, we reviewed the current evidence on the treatment of rosacea, provide a guideline (S1 level) and discuss the differential diagnosis of rosacea.